Computer-aided detection in mammography: applications and repercussions. - Ulissey MJ (Applied Radiology, 2006)
In the last several years, computer-aided detection (CAD) has been the subject of much research and development, but it has also engendered a great deal of controversy. Questions have been raised regarding the use of CAD, its utility, and its potential legal ramifications. Based on his experience and research, the author presents the applications and repercussions of CAD and discusses the controversies surrounding its use.